(untitled) (Journal of Economic Research & Business Administration, 2025)
This article presents a bibliometric analysis methodology focused on the application of artificial intelligence (AI) in accounting, conducted using international scientific databases such as Scopus, Web of Science, and Google Scholar, along with the VOSviewer analytical tool. The originality of the research lies in the systematization of approaches to the use of AI in automating accounting processes, enhancing the accuracy of financial control, and improving the efficiency of managerial decision-making. A total of 603 scientific publications were reviewed, with 269 highly cited articles selected from the Scopus database. The results demonstrate a steady increase in interest toward digital technologies in accounting, particularly in the automation of routine operations, digitization of financial reporting, internal auditing, tax accounting, and financial risk forecasting. Special attention is given to recent trends reflecting the expanding scope of AI in accounting and control. The study concludes by highlighting the potential for further research into the application of AI across various segments of accounting, including a comparative analysis of its impact on accounting efficiency in small and large businesses, as well as the assessment of risks associated with AI implementation in financial systems. Given the limited exploration of accounting digitalization in Kazakhstan, this area offers a promising direction for future academic inquiry. Key words: artificial Intelligence, accounting, accounting automation,bibliometric analysis.